2011
DOI: 10.1038/mp.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of UPF3B/NMD-deficient lymphoblastoid cells from patients with various forms of intellectual disability

Abstract: The nonsense-mediated mRNA decay (NMD) pathway was originally discovered by virtue of its ability to rapidly degrade aberrant mRNAs with premature termination codons. More recently, it was shown that NMD also directly regulates subsets of normal transcripts, suggesting that NMD has roles in normal biological processes. Indeed, several NMD factors have been shown to regulate neurological events (for example, neurogenesis and synaptic plasticity) in numerous vertebrate species. In man, mutations in the NMD facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 63 publications
6
141
0
1
Order By: Relevance
“…In patient 2 with autism, speech delay, and abnormal EEG, we have identified a de novo B1.0-Mb deletion in 4q21.23q21.3, harboring only one gene ARHGAP24 that encodes a Rho-GTPase-activating protein, regulating neuronal growth. Nguyen et al 20 showed that deregulation of ARHGAP24 inhibits axon and dendrite outgrowth and branching. A number of overlapping larger-sized deletions, ranging in size between 4.4 and 17.9 Mb have been found in patients with ASDs and DD 9 (case 5; Decipher patients 753, 994, (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In patient 2 with autism, speech delay, and abnormal EEG, we have identified a de novo B1.0-Mb deletion in 4q21.23q21.3, harboring only one gene ARHGAP24 that encodes a Rho-GTPase-activating protein, regulating neuronal growth. Nguyen et al 20 showed that deregulation of ARHGAP24 inhibits axon and dendrite outgrowth and branching. A number of overlapping larger-sized deletions, ranging in size between 4.4 and 17.9 Mb have been found in patients with ASDs and DD 9 (case 5; Decipher patients 753, 994, (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…ARHGAP24 regulates neuronal morphology. Notably, overexpression of ARHGAP24 in murine hippocampal neurons leading to decreased axon outgrowth, together with a reduction in the number of dendritic termini 293 . This suggests that ARHGAP24 could play a role in the development of dendritic spines but this has not yet been demonstrated.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…ARHGAP24 is a binding partner of filamin A, an F-actin crosslinking protein 292 . ARHGAP24 is a canonical target of the nonsense-mediated mRNA decay (NMD) factor UPF3B that regulates the degradation of mutated transcripts, and mutations in the genes coding for UPF3B have been linked to intellectual disability 293 . ARHGAP24 regulates neuronal morphology.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In humans, two UPF3 paralogs, UPF3 and UPF3X (also called UPF3A and UPF3B, respectively), differently modulate NMD activity (Chan et al, 2009;Kunz et al, 2006;Lykke-Andersen et al, 2000;Serin et al, 2001) in ways that, like UPF1 and another NMD factor, UPF2, have been shown to be crucial for, for example, normal neuronal maturation and development (Colak et al, 2013;Jolly et al, 2013;Laumonnier et al, 2010;Lou et al, 2014;Nguyen et al, 2012Nguyen et al, , 2013Tarpey et al, 2007). UPF3 or UPF3X are generally associated with exon junction complexes (EJCs; see below) that are deposited in the nucleus upstream of newly spliced exon-exon junctions, whereas UPF2 is generally associated with EJCs after newly synthesized mRNAs are exported to the cytoplasm (Kim et al, 2001;Lejeune et al, 2002;Lykke-Andersen et al, 2001).…”
Section: Central Nmd Factors In Human Cellsmentioning
confidence: 99%